An Analysis of Student Engagement for Online Microeconomics Class Based on ELED - Melati, Inaya Sari; Harnanik, Harnanik (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aims to analyze the factors affecting student engagement in Microeconomics online classes based on E-Learning Engagement Design (ELED). This study applied a mixed method with a sequential model. The study population included all students of the Department of Economics Education UNNES who took online courses in Microeconomics and Microeconomics 1, both regular and international classes, with a total of 320 students and 4 lecturers handled the classes. The results showed that situational interest, personal significance, mastery of self-talk and mastery of self-talk for performance had a positive effect on student engagement in Microeconomics online classes. Meanwhile, mastery of self-talk to avoid negativity, environmental control, independent consequences, and setting proximal goals do not significantly influence student engagement in Microeconomics online classes. The concept of E-Learning Engagement Design (ELED) has been applied to all components. However, it is necessary to standardize the learning environment components to make sure there is no gap among Microeconomics classes which leads to less optimal academic services.